Issues and open questions of greenhouse gas emission trading under the Kyoto protocol - Michael Dutschke; Axel Michaelowa (Hamburg Institute of International Economics (HWWA), 1998)
For the first time, the Protocol negotiated by the third Conference of the Parties to the U.N. Framework Convention on Climate Change in Kyoto sets legally binding emission targets for the commitment period 2008-2012 for the industrial countries and countries in transition listed in Annex I. These targets encompass a basket of six greenhouse gases and do not have to be reached by domestic emission reduction alone. The Protocol allows the use of less costly emission reduction potential abroad through four mechanisms: common targets or "bubbles" (Art. 4), emission trade (Art. 17), Joint Implementation (Art. 6) and projects of the "Clean Development Mechanism" (CDM) with countries without emission targets (Art. 12). Bubbles withstanding they shall be "supplemental" to domestic measures. Supplementarity has not been defined in the Protocol, though. If average emissions in the commitment period are lower than the emission target the difference can be banked for the next commitment period. Due to time pressure during negotiation of the Protocol rules for the use of flexibility mechanisms remain vague. Thus the next Conference of the Parties has to settle many details. This study makes suggestions for the solution of these open issues on the base of the goal of economic efficient emission reduction. It also considers the political feasibility of these suggestions.
Keywords: 330; Klimaschutz; Internationale Umweltpolitik; Umweltzertifikat; Kohlendioxid; Welt